The Influence of Price, Product Quality and Promotion on Customers Purchase Intention of Pasteurized Milk Products - Frans Sudirjo; Tengku Kespandiar; Agus Nurofik; Septianti Permatasari Palembang; Miranti Pradipta Utami (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study uses the multiple linear regression method using the SPSS 20 application. Results of the equation Y = - 5.130 + 0.249X1 + 0.747X2 + 0.409X3 for multiple linear regression. There is a partial effect of product quality (X1) on consumer buying interest, according to the findings of the t-test on the product quality variable (X1) (t-count value of 5.220 > t-table value of 1.992). (Y). There is a somewhat significant influence of promotion on consumer buying interest, as indicated by the promotion variable's (X2) t-count value of 7,379 > t-table 1,992. (Y). There is a relationship between the price of pasteurized milk and consumer purchasing interest, as indicated by the price variable (X3) having a t-count value of 2,304 > t-table 1,992. (Y). Partly, and the results of the F test show that there is an effect of product quality (X1), promotion (X2), and price (X3) of milk on consumer buying interest (Y) at the same time (f-count value of 170.823 > f-table 2.73). (simultaneously).